Sex Work, Injection Drug Use, and Abscesses: Associations in Women, But Not Men. (4th October 2017) - Burke, Deirdre; Wurcel, Alysse; Landy, David; Skeer, Margie; Heimer, Robert; Chui, Kenneth K. H; Stopka, Thomas
Abstract: Background: Abscesses are a common health issue for people who inject drugs (PWID). Females have a higher risk of abscesses, yet it is unclear if the risks are comparable among female sub-populations. The goal of this study was to examine the associations between gender, sex work, and risks of abscesses in PWID. Methods: We combined data from two cross-sectional studies conducted in the greater Boston area with 225 participants aged 18–45 years, who participated in injection drugs use in the previous 30 days. Demographics, injection-mediated risks, and sexual behaviors were collected using ACASI. Injection drug use was defined as "high" if injection frequencies exceeded the median. Odds ratios from multivariable logistic regressions were used to represent the associations; all analyses were gender-stratified. Results: The cohort was 31% women (71/225). White race was more common in women than men (89% vs. 63%). Women were more likely than men to report: sex work 31% vs. 14%, heavy heroin use 56% vs. 40%, HCV 76% vs. 61%, abscesses 54% vs. 38%. Controlling for confounders, females who engaged in sex work had >7 times higher odds of reporting abscesses [AOR 7.51; 95% CI (1.41, 40.07)]. There was no association between sex work in men and increased risk for abscess. Conclusion: We found a gender-specific association between sex work, injection drug use, and abscesses among PWID. The cross-sectional designs precluded causal inferences; further longitudinal studies are necessary to better understand the gender-associated risks for abscesses and to develop harm reduction interventions. Disclosures: A. Wurcel, Tufts Medical Center, Tufts University School of Medicine: Grant Investigator, Grant recipient, Merck, BMS and Research support